2000
DOI: 10.1108/01437730010325031
|View full text |Cite
|
Sign up to set email alerts
|

Leadership for strategic change

Abstract: Organizations in need of strategic turnaround often seek charismatic leaders to lead change efforts. With the growing popularity of democratizing workplaces, team‐based approaches to strategic change are emerging. The literature on each of these change approaches is reviewed. Several research propositions are offered which suggest that strategic teams can be a better choice than charismatic leaders for turning around an organization. The authors also note the need for future research to compare the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 20 publications
0
20
0
3
Order By: Relevance
“…Other potential substitute variables will certainly be added, although we note that the literature on strategic change does contain references to the use of team based approaches. In fact, one of us proposed in an earlier paper that a team approach to initiating and guiding organizational change efforts can substitute for certain types of charismatic leadership (Landrum, Howell, & Paris, 2000). We certainly encourage researchers and theory builders who focus on strategic leadership to include potential substitutes for leadership in their models and research.…”
Section: Renaissance Of Substitutes For Leadership Theorymentioning
confidence: 95%
“…Other potential substitute variables will certainly be added, although we note that the literature on strategic change does contain references to the use of team based approaches. In fact, one of us proposed in an earlier paper that a team approach to initiating and guiding organizational change efforts can substitute for certain types of charismatic leadership (Landrum, Howell, & Paris, 2000). We certainly encourage researchers and theory builders who focus on strategic leadership to include potential substitutes for leadership in their models and research.…”
Section: Renaissance Of Substitutes For Leadership Theorymentioning
confidence: 95%
“…Some authors explicitly do not mention CEO transformational leadership as a necessary ingredient for turning a new strategy into organizational performance (e.g., Mankins & Steele, 2005). Moreover, Landrum, Howell, and Paris (2000) claim that charismatic leaders -a concept closely related to transformational leadership (Bass, 1985;Conger & Kanungo, 1998) -may not be a universal remedy for organizations (see also Khurana, 2002). Accordingly, Tosi, Misangyi, Fanelli, Waldman, and Yammarino (2004) found that CEO charisma did not relate to any firm performance measures.…”
Section: Introductionmentioning
confidence: 97%
“…With the growing popularity of democratization in the workplace, team-based strategic change approaches are emerging. Strategic teams may be a better option than charismatic leaders to change an organization (Landrum, Howell & Lori, 2000). There are seven different approaches to structuring and managing the change that organizations can take to improve the likelihood of driving a successful transform in their organizations (Schell, 2019).…”
Section: C) Leadership and Organizational Performancementioning
confidence: 99%